The Emergence of Mucormycosis in Free-Ranging Marine Mammals of the Pacific Northwest - Huggins, Jessica L.; Garner, Michael M.; Raverty, Stephen A.; Lambourn, Dyanna M.; Norman, Stephanie A.; Rhodes, Linda D.; Gaydos, Joseph K.; Olson, Jennifer K.; Haulena, Martin; Hanson, M. Bradley (Frontiers in Marine Science, 2020)
Primary fungal diseases in marine mammals are rare. Mucormycosis, a disease caused by fungi of the order Mucorales, has been documented in few cetaceans and pinnipeds. In 2012, the first case of mucormycosis in the Pacific Northwest was documented in a dead stranded harbor porpoise (Phocoena phocoena) in Washington state. Since then, mucormycosis has been detected in a total of 21 marine mammals; fifteen harbor porpoises, five harbor seals (Phoca vitulina), and one southern resident killer whale (Orcinus orca). Infected animals were predominately found in the inland waters of Washington and British Columbia, and one harbor seal was recovered in northern Oregon. Fungal hyphae were detected histologically in a variety of tissues, including brain, lung, spleen, pancreas, kidneys, muscle, lymph nodes, and skin. Three fungal species were identified from seven cases by PCR screening or fungal culture; Rhizomucor pusillus (four cases), Lichtheimia corymbifera (two cases), and Cunninghamella bertholletiae. Underlying conditions such as emaciation, current or recent pregnancy, multisystemic parasitism, protozoal infection, and herpesvirus were found in several affected animals. Reasons for the appearance and subsequent increase of these fungal infections in marine mammals are unknown. The emergence of this disease as a source of marine mammal mortality in the Pacific Northwest is of particular concern for endangered southern resident killer whales that spend time in this region. Current population-level stressors such as insufficient prey, high levels of contaminants, and noise pollution, could predispose them to these fatal infections.